EU options on Russia and the Eastern partners: "Cooperative confrontation" as the guiding principle beyond the Riga Summit - Kai-Olaf Lang; Barbara Lippert (Stiftung Wissenschaft und Politik (SWP), 2015)
Moscow's hegemonic stance on the post-Soviet space and its provocations in Ukraine force the European Union to find strategic clarity in its eastern neighbourhood. Often in the midst of discontinuous internal reform processes, the countries to the Union's east find themselves hanging between a vague "wider Europe" proposal from Brussels and Moscow's increasingly forceful idea of a "wider Russia". At the May 2015 Riga Summit the EU heads of state and government will meet with their counterparts from the Eastern Partnership, including the new associates Moldova, Georgia and Ukraine. The EU should grant these countries political guarantees, material assistance and European perspectives. But the European Union can only develop bilateral and plurilateral European perspectives if it faces up to the Russian factor and realigns its relations with Moscow on the Eastern Policy triangle of stability, cooperation and norm-driven transformation. (SWP Comments)
Keywords: 320